PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SEKOLAH DASAR NEGERI 007 SEKAR MAWAR KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Asriyanti, Asriyanti; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: This research aims to improve grade IV student’s social science contextual teaching learning at SD 007 Sekar Mawar Kecamatan Pasir Penyu Kabupaten Indragiri Hulu academic year 2014/2015 trought “ Application of contextual teaching learning grade IV students social science learning achievement at SD Negeri 007 Sekar Mawar. This research was conducted in mart. The numbers of students are 25 students which contains of 12 boys and 13 girls. This research is classroom action research which contains of three cycles. Each cycle consist of 2 meeting. Parameter of the research is involved students learning achievement after the action in each cycle (daily test I, II, III). Instrument of the research contains of learning tools ( syllabus, RPP, LKS, Learning result paper sheet), observation of student and teacher activity sheet. Data of the research will analyze descriptively. Research data show that learning achievement has increased. Where prior to the application of the methods of giving a task as much as any 13 students (52%) scored daily test is above or equal to the minimum completeness criteria (KKM). It was improved to 76% after using the application of the method of giving a task in first cycle. In the second cycle increased to 92%. Activities of the student during the learning process is can be categorized very well. From the explanation above show that application of the method of contextual teaching learning (CTL) can be improving grade IV student’s social science learning achievement at SD Negeri 007 Sekar Mawar.Keyword : the method contextual teaching learning